Sensibilidade de teca (Tectonas grandis L. f.) a matocompetição e a herbicidas - Domingos Júnior, Fausto Antônio (2014)
Invasive plants have been a limiting factor for the initial establishment of planted forests, especially when that occurs over degraded grazing areas with Brachiaria spp. Two studies were done to determine the impact of weeds, and its control, on teak establishment. The first one evaluated teak growth under the influence of Brachiaria decumbens. Treatments were no weed control, complete control of weeds, weed control after 6 months of competition, and weed control in a 30 cm radius around the seedlings. The experiment was done in a grazing area, containing Brachiaria decumbens, on May 2012. The experimental design was randomized blocks, with four treatments and four replications. Twenty two months after transplanting, all treatments in which teak co-existed with the invasive weed, had their growth affected. Complete weed control is required to assure best teak development. The second study evaluated different herbicides for their toxicity to teak (Tectona grandis L.f.) seedlings. The experiment was done in degraded grazing area containing Brachiaria decumbens and tifton 85 (Cynodon spp.). Treatments consisted of ten herbicides, five pre-emergent, and five post-emergent, and a control that was sprayed with water. The experimental design was completely randomized, with ten replications. Herbicides were sprayed thirty days after transplanting. The herbicide clorimurom-ethyl (Panzer 250 WDG®), hexazinone (Magnus BR®), hexazinone (Hexazinona®), haloxifop-R, methyl ester (Verdict R®), fomesafem + fluazifope + fluasifope-p-buthyl (Fusiflex®) were phytotoxic, but did not kill the seedlings; all others killed most seedlings.